Educational administration needs a new model for the future - Benedict, Gary (Education quarterly.)
This administrative model is an economical method of approaching administrative problems. To be sure the substantive content of problems and the situational factors surrounding them will differ but can be approached intelligently by application of an administrative model. Knowledge of the administrative process and the ability to apply an appropriate model do much to make for effective administration.